Measurement of the equivalent friction coefficients of ball bearings based on the variations in kinetic energy - Panlong Wu; Chunlei He; Zhiyang Ren; Qiang Feng; Guang Chen; Chengzu Ren (Friction)
Friction energy consumption is the primary cause of energy loss in rolling bearings, and friction characteristics are critical indicators of rolling bearing quality. To comprehensively understand the friction characteristics of ball bearings, the equivalent friction coefficient was proposed, and a reliable measurement method was studied. This new solution addressed the difficulty of measuring the friction characteristics of ball bearings highlighted by friction torque. The angular speeds of various components in the rolling bearings were derived using a quasistatic approach. The angular speed relationships among various components of the rolling bearings were subsequently analyzed. A kinetic energy dissipation model for the measuring system was ultimately obtained. A novel apparatus for measuring the rolling bearing equivalent friction coefficient was established. The spindle only underwent angular speed attenuation due to friction of the tested bearing without the use of power, and the variation in kinetic energy was monitored in real time with a high-precision speed sensor. After that, the equivalent friction coefficients of the measured bearings were examined. The effects of speed, load, and lubrication on the equivalent friction coefficient of the tested bearing were studied. The findings demonstrated that, to some extent, the equivalent friction coefficient increased with an increase in spindle speed and decreased with increasing load. The equivalent friction coefficient also increased with increasing kinematic viscosity of the lubrication oil, and the friction coefficient for dry friction was greater than that with 50 oil (with a kinematic viscosity of 50 mm2/s) but slightly lower than that with 70 oil (with a kinematic viscosity of 70 mm2/s). With this method, an accurate and comprehensive understanding of the friction characteristics of ball bearings is achieved.